Science and technology as a tool for poverty reduction and socio-economic development in ECOWAS communities (2010)
Poverty reduction and economic development have been known to be positively correlated to technological development. On the other hand, studies have shown that government policies directly affect indigenous technological growth and this ultimately impacts the socio-economic well being of a country. even though blessed with abundant human and natural resources, African has for along time been a dumping ground for foreign technology and this has stifled any possibility of serious technological growth that can reverse the trend. economic model from asian countries like China, india and south-korea reveal a significant and positive correlation between indigenous technological growth and poverty reduction. To achieve any meaningful development for ECOWAS countries in the 21st century world, there is need for the creation of an enabling environment through favorable government policies and other incentives for indigenous technology to grow. this in turn would create jobs: ensure food security and sustainable development.